MEMOSISIKAN SASTRA SIBER SEBAGAI LAHAN BARU DALAM PENELITIAN SASTRA MUTAKHIR DI INDONESIA - Rejo, Uman (Paramasastra, 2014)
Cyber literature is literature that covers various genres of work submitted through the  electronic  media.  Ideology  contains  in  the  literature  cyber  is  postmodern ideology. Postmodern  is difficult to be  identified specifically, but the postmodern has  common  traits  that  always  builds  sorting  binary  opposition.  In  the  current literary  research,  literary  cyberspace  is  not  a  study,  but  rather  a  ?study  area?. Cyber  is  the study of  literature, not as a ?perspective?. As study materials, cyber literary  phenomenon  presents  a  unique,  creative,and  challanges  a  literary researcher. Therefore, the  field  is classified as current work, should use  the  latest research model, which is more significant if it is utilized.